2021
DOI: 10.1093/eurjpc/zwab186
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and young adult body mass index for predicting the risk of developing adult heart failure in men

Abstract: Aims Hospitalizations for heart failure among young adults and middle-aged individuals have increased. The aims of the present study were to evaluate the association between birth weight and risk of adult heart failure and the importance of change from low birth weight to overweight/obesity at young adulthood. Methods and results We used the population-based body mass index (BMI) Epidemiology Study cohort Gothenburg (n = 35 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Members of our research group and others have previously studied the prevalence of obesity [30][31][32], and its association with mortality [33,34] and cardiovascular health [8,[35][36][37][38][39]. Still other researchers have demonstrated that heart rate and blood pressure at conscription may be linked to the risk of psychiatric disorders later in life [23,40].…”
Section: Discussionmentioning
confidence: 99%
“…Members of our research group and others have previously studied the prevalence of obesity [30][31][32], and its association with mortality [33,34] and cardiovascular health [8,[35][36][37][38][39]. Still other researchers have demonstrated that heart rate and blood pressure at conscription may be linked to the risk of psychiatric disorders later in life [23,40].…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Small for gestational age infants display high and early onset rates of hypertension (immature nephrogenesis results in the development of kidneys with a reduced number of filtrating units known as nephrons), stroke and diabetes in adulthood. [19][20][21][22] Also the prevalence of coronary artery disease is higher in these people than in their peers born with normal weight in the medium and long term. 23 An inverse and independent of body mass index (BMI) relationship between low birth weight and stroke among adult men has recently been described.…”
Section: Early Oxidative Stress and Maternal Healthmentioning
confidence: 92%
“…Small for gestational age infants display high and early onset rates of hypertension (immature nephrogenesis results in the development of kidneys with a reduced number of filtrating units known as nephrons), stroke and diabetes in adulthood 19–22 …”
Section: Early Oxidative Stress and Maternal Healthmentioning
confidence: 99%
“…Restricted and excessive fetal growth, as reflected in small and large for gestational age (SGA and LGA, respectively), have been linked to increased risks of cardiovascular diseases (CVD), including hypertension, ischemic heart disease (IHD), stroke, heart failure, and other cardiometabolic disorders in childhood and adulthood . Short gestational age, as reflected in preterm birth, was also found to be associated with increased risks of IHD, stroke, and heart failure, irrespective of fetal growth .…”
Section: Introductionmentioning
confidence: 99%